Respiratory symptoms of exposure to substances in the workplace among dental laboratory technicians - Iliyana Stoeva (Nofer Institute of Occupational Medicine, 2021)
Background As dental technicians are exposed to a variety of airborne chemicals that can act as irritants and sensitizers, and may give rise to work-related respiratory symptoms, the aim of this study was to estimate the prevalence of respiratory symptoms of exposure to substances in the workplace and associated risk factors in dental laboratory technicians. Material and Methods A cross-sectional study was performed among 539 dental technicians in the Plovdiv region using a self-report questionnaire. A multiple logistic regression analysis was performed in order to investigate the relationship between sex, work experience, daily exposure to chemicals from the dental environment, and a history of atopic disorder with work-related respiratory symptoms. Results A total of 539 dental technicians completed the questionnaire. The prevalence of self-reported work-related respiratory symptoms was 26.2%. Based on logistic regression, the most significant factors associated with work-related respiratory symptoms were daily exposure of >8 h (OR = 5.83, 95% CI: 1.96-17.34) and the lack of a ventilation system (OR = 4.26, 95% CI: 2.39-7.58). Dental technicians with work experience of 20 years. A personal history of asthma (OR = 3.74, 95% CI: 1.39-10.07), allergic rhinoconjunctivitis (OR = 2.10, 95% CI: 1.29-3.41) and atopic dermatitis (OR = 2.32, 95% CI: 1.23-4.38) was also associated with work-related respiratory symptoms. Conclusions The findings of this study suggest that work-related respiratory symptoms are frequent among dental technicians and occur early in their career. A more comprehensive study should be conducted throughout the country in order to estimate the prevalence, and to establish effective programs and techniques of preventing work-related respiratory symptoms in dental technicians. Med Pr. 2021;72(2):105-11